Why do you need to read fiction? The role of transportation through fiction reading in improving perspective taking - Nurinas Dzakiyah Firman; Lukman Lukman; Faradillah Firdaus (University of Muhammadiyah Malang, 2022)
Late adolescents are reported to have poor perspective-taking. This study aimed to determine whether an improvement to perspective-taking is achieved after participants read fiction, and whether a transportation process is involved in it. The participants in this study were late adolescents (17-22 years old) with poor perspective-taking and certain degrees of experience and interest in reading fiction (N = 8). This study used a pretest-posttest-follow-up design. The Friedman test results show that there is a significant difference in the perspective-taking scores of participants before and after receiving manipulation in the form of supply of fiction reading media (p = 0.002, ̄x pretest = 11, ̄x posttest = 37.25, ̄x follow-up = 37.1). The simple regression analysis test results show that the improved perspective-taking is not influenced by the occurrence of transportation in participants when reading fiction (p = 0.072, r = 0.175, β = 0.473). The participants showed improved perspective-taking right after the manipulation treatment was given, but slightly declined in the subsequent week.